Industrial Biotechnology - Benvenuto, Mark Anthony (De Gruyter, 2019)
The book provides an excellent introduction to industrial biotechnology, addressing the applications of biomolecules and living systems in industrial manufacturing of various products. Each part of the book is devoted to a certain biotech sector, such as biofuels, food, chemicals, pharmaceuticals and materials. The book also covers the environmental aspects of industrial biotechnology and the principles of bio-based economy. - Resumé vydavatel
Keywords: průmyslová biotechnologie -- environmentální aspekty; industrial biotechnology -- environmental aspects; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)